Support and adsorbent materials for anaerobic digestion: enhancing process stability and nutrient control (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Anaerobic digestion is a technology applied to wastewater treatment and the production of biogas as a renewable energy source. However, it exhibits limitations in the removal of nutrients such as nitrogen and phosphorus, which can lead to eutrophication. Various support materials have been evaluated for their capacity to stabilize the process, enhance biogas production, and facilitate nutrient adsorption. This literature review analyzed the characteristics, mechanisms of action, efficiency, environmental impact, and economic feasibility of different materials applied in anaerobic digesters. The findings indicate that dual-function materials, those providing microbial support and adsorptive capacity, such as biochar and zeolite, achieve superior overall performance. In conclusion, material selection should consider technical efficiency, the target nutrient to be removed, and local availability, with biochar and zeolite emerging as promising options to optimize anaerobic digestion in sustainable contexts such as Ecuador.